CYKLE REPRESYJNOŚCI W STANACH ZJEDNOCZONYCH AMERYKI PÓŁNOCNEJ I UNII EUROPEJSKIEJ A POPULIZM - Stępniak, Piotr (Wydział Prawa i Administracji UAM, 2009)
The paper is an attempt to compare factors that are conducive to populist movements observed in the United States, the European Union and Poland, and to identify the influence they have on the State’s penal policy. The analysis is made against the background o f the current state of repression which followed the terrorist attacks in the US on 11 September 2001 and resulted in a new political, economic and social situation. Those events had an impact on the social will to institute a more severe penal system in each o f the analysed states. However, the reasons for populist attidudes present in the EU member states are weaker than in the US. As a result, their penal, or represson system today is less punitive. Those deliberations on the American and European populist movement have triggered off the question why such populist ideas are engaged in arguments proposing a more severe penal system in Poland. The results o f empirical studies show that Poland’s current system o f penal repression cannot be justified by the populist attitudes of the Polish society whose will to penalise is not as strong as in other states. It seems that in Poland today penal policy has become a subject o f political manipulation where less politically sophisticated public opinion is used to justify its decisions.
POPULISM AND CYCLES OF REPRESSION IN THE US AND THE EU